2018
DOI: 10.1194/jlr.p081281
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of molecular lipid species predict long-term clinical outcome in coronary artery disease patients

Abstract: Purpose: We investigated the associations of ten previously identified high risk molecular lipid species and three ceramide ratios with the occurrence of major adverse cardiac events (MACE) during a median follow-up of 4.7 years in patients with coronary artery disease (CAD). Methods:Between 2008 and 2011, 581 patients underwent diagnostic coronary angiography or percutaneous coronary intervention for stable angina pectoris (SAP) or acute coronary syndrome (ACS).Blood was drawn prior to the index procedure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 34 publications
6
92
0
2
Order By: Relevance
“…The findings were first documented in the LURIC study [23] and replicated in the ATHEROREMO-IVUS study [28,29]. FINRISK 2002 study, Corogene study, PREDIMED trial, ADVANCE study, and LIPID study consistently confirmed the findings [24,26,[30][31][32].…”
Section: Yesmentioning
confidence: 66%
See 3 more Smart Citations
“…The findings were first documented in the LURIC study [23] and replicated in the ATHEROREMO-IVUS study [28,29]. FINRISK 2002 study, Corogene study, PREDIMED trial, ADVANCE study, and LIPID study consistently confirmed the findings [24,26,[30][31][32].…”
Section: Yesmentioning
confidence: 66%
“…As to methods of lipid measurement, two early studies used shotgun lipidomics [19,20], two studies used NMR measuring total lipids, triglycerides, and cholesterol within l4 lipoprotein subclasses [21,22], and the majority of studies used LC-MS, measuring hundreds of lipids [16][17][18][19][20][21][22][23][24][25][26][27]. Eight of the 16 studies were lipidomics/metabolomics-wide association studies that assessed associations of all measured lipids with CVD outcomes [19][20][21][22][23][24][25][26], six studies used a candidate-lipid approach by focusing on specific lipids such as ceramides [27][28][29][30][31][32], and two studies classified lipids into groups and examined global associations of lipid species with CVD outcomes [33,34]. Of the 16 studies, 6 studies included participants with a history of coronary heart disease (CHD) and focused on secondary prevention [23,24,26,28,29,31], and 10 studies focused on primary prevention of CVD [19][20][21][22]25,…”
Section: Summary Of Recent Studies On Lipidomics For Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent cardiovascular studies have consistently shown an increased risk of adverse vascular events and mortality in individuals with increased ratios of long-chain to very long-chain ceramides in plasma. 5,17,[31][32][33] In a murine model of ceramide synthase 2 haploinsufficiency, a reduction in levels of very long-chain (C22:0 and C24:0) ceramides and a compensatory increase in levels of longchain ceramides (C16:0) was noted, resulting in an increased susceptibility to insulin resistance and hepatocyte apoptosis. 30 Given the role of ceramides in pancreatic b-cell dysfunction, insulin resistance and vascular reactivity, 34 increased cardiometabolic risk could potentially mediate the association with dementia.…”
Section: Discussionmentioning
confidence: 99%